2013
DOI: 10.1007/s00421-013-2734-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an even-pacing strategy on exercise tolerance in well-trained cyclists

Abstract: By adopting an uneven, parabolic distribution of work, cyclists in this study were able to achieve an average intensity during self-paced exercise in excess of their maximum sustainable power output. A subsequent matched even-paced bout resulted in cumulative metabolic stress that could not be managed by moment-to-moment changes in power output. These results challenge the notion that strict even pacing is optimal for endurance time trial events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Comparative data on TTE and TT performances are limited (Amann, Hopkins & Marcora, 2008;Ham & Knez, 2009;Thomas, Stone, St Clair Gibson, Thompson & Ansley, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative data on TTE and TT performances are limited (Amann, Hopkins & Marcora, 2008;Ham & Knez, 2009;Thomas, Stone, St Clair Gibson, Thompson & Ansley, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al (2013) showed that though even pacing might theoretically be optimal for endurance performance (De Koning et al, 1999), but in athlete's reality a parabolic shaped pattern might be more appropriate since the cyclists in their study were not able to finish the race when forced into an even paced pattern. In addition, it is important to note that these findings are from cyclists, as differences in optimal pacing might exist between different sports due to their specific characteristics (Stoter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, large variations in power output to counteract external perturbations such as topography and wind (discussed in “Environmental factors” below) are required to maintain an even pacing strategy. Such changes in power output have been shown to increase physiological strain and reduce performance 69. Under such circumstances, variations in speed to maintain a relatively even distribution of power output/energetic resources may likely be a more optimal strategy for athletes.…”
Section: Factors Influencing Pacing In Triathlonmentioning
confidence: 99%